1982
DOI: 10.1524/zkri.1982.158.12.53
|View full text |Cite
|
Sign up to set email alerts
|

The derivative structure of silicate garnets in grandite

Abstract: The crystal structures of birefringent silicate garnets have been studied using crystals from three different localities: North Moravia, Czechoslovakia, (Ca2.96Fe0 04) (Al16oFeo.4o) (Si2.94Alo.oe) °i2> Munam, North Korea (Ca2.91Mn0.05Fe0.04) (Alj.33Fe0.65Ti0.02) (Si2.97Alo.03) 012, and Kamaishi, Japan, (Ca2.98Mn0.02) (Alo^Fe, 16) (Si2.93Al0 07) 012. Cell dimensions show salient features which include (1) one of the axial angles, of which we chose β, is significantly deviated from 90°: 90.07(1)° for Moravia gar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 11 publications
1
8
0
Order By: Relevance
“…And last two chosen criterions are R B and R F reliability factors, whose values should be at least better than those obtained for the Ia 3d space group (Supplementary Material 6, third row). Namely, distances, sofs, and lower comparative R-values were most of the decisive factors for the space group definition in vast majority of the previously studied low symmetry ugrandites (Takéuchi et al, 1982;Allen and Buseck, 1988;Wildner and Andrut, 2001;Shtukenberg et al, 2005;Frank-Kamenetskaya et al, 2007). Beside these, for accessory criterions, there were chosen their estimated standard deviations (e.s.d.s).…”
Section: B Crystal Structure Refinementsmentioning
confidence: 99%
See 2 more Smart Citations
“…And last two chosen criterions are R B and R F reliability factors, whose values should be at least better than those obtained for the Ia 3d space group (Supplementary Material 6, third row). Namely, distances, sofs, and lower comparative R-values were most of the decisive factors for the space group definition in vast majority of the previously studied low symmetry ugrandites (Takéuchi et al, 1982;Allen and Buseck, 1988;Wildner and Andrut, 2001;Shtukenberg et al, 2005;Frank-Kamenetskaya et al, 2007). Beside these, for accessory criterions, there were chosen their estimated standard deviations (e.s.d.s).…”
Section: B Crystal Structure Refinementsmentioning
confidence: 99%
“…phase transition from the Ia 3d to the R 3c, Fddd, C2/c, and I 1 space groups (Hatch and Griffen, 1989) and also in conformity with our previous results. However, because some confusion arises due to the different monoclinic settings in previous papers (Takéuchi et al, 1982;Gali, 1983;Hatch and Griffen, 1989;Wildner and Andrut, 2001), we shall also include the I2/c space group for further reconsideration too. Therefore, the remaining solutions that should be considered are R 3c, Fddd, I2/c, and C2/c space groups.…”
Section: B Crystal Structure Refinementsmentioning
confidence: 99%
See 1 more Smart Citation
“…review of the literature Brauns (1891) summarized optical studies of birefringent sector-zoned crystals of garnet. Takéuchi et al (1982) found that Al 3+ and Fe 3+ ions are distributed at the octahedral sites in an ordered manner. The birefringence was attributed to a lowering of the symmetry of garnet to orthorhombic (Fddd) or triclinic (I1).…”
mentioning
confidence: 97%
“…The birefringence was attributed to a lowering of the symmetry of garnet to orthorhombic (Fddd) or triclinic (I1). Rossman & Aines (1986) studied the sample of Takéuchi et al (1982) by FTIR and found that the distribution of OH is isotropic. Allen & Buseck (1988) described a non-isotropic distribution of OH groups in anisotropic garnets.…”
mentioning
confidence: 99%